Utilitarian Shopping Motives and Reference Groups on Online Fashion Product Purchase Decisions - Fitriani Latief; Asniwati (Jurnal Economic Resource, 2021)
This study aims to examine shopping utility motives and the reference group that influences purchasing decisions. This research approach uses a scientific approach. The population in this study was all students of STIE Nobel Indonesia class 2016, 2017, and 2018 with 418 people. The criteria for this research are students of STIE Nobel Indonesia Makassar class 2016, 2017, and 2018 who have bought online fashion products with the Slovin formula to calculate the sample size of a known population of 205 people. Multiple linear regression statistical analysis with the help of SPSS used to process research data. Based on the results of research and discussion on the Influence of Utilitarian Shopping Motives and Reference Groups on Online Fashion Product Purchase Decisions (Study on Students of STIE Nobel Indonesia Makassar), several conclusions can be drawn; there is a positive and significant influence on the independent variable, namely the utilitarian shopping motive variable and the reference group partially. on the dependent variable, namely the purchase decision. This study suggests that companies should use reference groups for consumers in consumer decisions to buy fashion products. Then, future researchers should conduct the same research supported by making more observations by adding other supporting variables, such as hedonic motivation, lifestyle, consumer attitudes, and others.